The Urgency of Moral and Ethical Education for Female Students of Ma'had Al-Bayyinah Tambun Selatan - Muthmainnatus Sa’diyah Mamu; Risalatul Muawanah; Zika Malik Juliana (Konsultan Jurnal Ilmiah Indonesia, 2026)
This study aims to examine the urgency of moral and character education among female students (santriwati) at Ma’had Al Bayyinah Tambun Selatan and its implementation in daily life. This research uses a qualitative approach with data collected through literature study, observation, and interviews involving approximately 50% of the students. The results show that most students understand morality as good behavior and proper manners, although some still lack deeper understanding. Almost all respondents consider moral education to be very important, even obligatory. The implementation of moral values is reflected in daily activities such as respecting teachers, maintaining polite speech, and being disciplined. The findings also indicate that the ma’had environment plays a significant role in shaping students’ character, while peer influence is the most dominant factor. Therefore, continuous guidance and a supportive environment are needed to strengthen moral education.